Notes on Madagascan Stoneflies (Plecoptera: Notonemouridae) - Zwick, Peter (Zootaxa, 2015)
Madagascar is inhabited by the single stonefly genus, Madenemura Paulian (= Tsaranemura Paulian, new synonymy). The original material of R. Paulian and the types of all nominal species proposed by him are lost. The type species, M. capuroni Paulian is distinct but material is presently not available. Madenemura andringitrensis Paulian (= M. perrieri Paulian, new synonymy), M. descarpentriesi Paulian, and M. culminalis Paulian are redescribed from subjectively identified fresh material. Madenemura pauliani new species is named from two females with overlong ovipositor. Madenemura bezanozano Paulian and M. stuckenbergi Paulian are doubtful species that cannot be recognized among the presently available material.